Association of Serum Inflammatory Cytokines with Left Ventricular Diastolic Dysfunction in Type 2 Diabetes Mellitus: A Clinical and Community-Based Cross-Sectional Study - Nomira Waheed, Javed Khurshed Shaikh, Muhammad Hashim Kalwar, Azal Jodat, Anam Arshad, Razwan Ashraf (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Left ventricular diastolic dysfunction (LVDD) is a frequent but under-recognized cardiac complication in patients with type 2 diabetes mellitus (T2DM). Inflammation is increasingly implicated in the pathogenesis of diabetic cardiomyopathy, yet few studies have quantified its relationship with echocardiographic diastolic indices. This study investigates the association between serum inflammatory cytokines and LVDD in T2DM patients. Methods: This multicenter, cross-sectional study was conducted from June 2022 to June 2023 at Rawal Institute of Health Sciences (Islamabad), Farooq Hospital DHA (Lahore), and Aziz Bhatti Shaheed Teaching Hospital (Gujrat). A total of 150 T2DM patients underwent echocardiographic assessment for diastolic function and were stratified into normal or LVDD (Grades I–III) groups. Serum levels of IL-6, TNF-α, high-sensitivity C-reactive protein (hs-CRP), and neutrophil-to-lymphocyte ratio (NLR) were measured. ANOVA, Pearson’s correlation, and multivariate logistic regression were used for analysis. Results: LVDD was present in 60% of participants. IL-6, TNF-α, hs-CRP, and NLR levels rose significantly with increasing LVDD grade (p < 0.001). IL-6 (r = 0.65), TNF-α (r = 0.60), hs-CRP (r = 0.55), and NLR (r = 0.58) showed strong positive correlations with E/e′ ratio. In multivariate analysis, IL-6 (OR 1.45, p < 0.001) and NLR (OR 1.80, p = 0.001) were independent predictors of LVDD. Conclusion: Systemic inflammation, particularly elevated IL-6 and NLR, is significantly associated with the severity of diastolic dysfunction in T2DM patients. These markers may serve as accessible tools for early detection and risk stratification of diabetic cardiomyopathy, warranting further prospective validation. Keywords: Type 2 diabetes mellitus, IL-6, TNF-α, NLR, diastolic dysfunction, echocardiography, inflammation.